Analisis Hukum Mengenai Wanprestasi Yang Dilakukan Debitur Terhadap Perjanjian Kredit Dengan Bank (Studi Putusan Nomor: 290/Pdt.G/2021/Pn Mdn) - Chirunnisa, Siti; Isnaini, Isnaini; Hidayani, Sri (Universitas Medan Area, 2024)
The credit agreement is binding on both parties. The offending party, especially those who do not comply with the agreement, will be subject to binding legal regulations and consequences. Legal consequences that must be borne by the offending party can be in the form of contract cancellation, compensation, and even fines. The research method used is normative juridical by conducting a case approach to Decision number 290/Pdt.G/2021/PN Mdn and related laws and regulations. The data analysis used is descriptive analysis with an approach to primary data and secondary data. The result of the research is that the legal rules regarding defaults on credit agreements are regulated in Article 1238 of the Civil Code. The mechanism for granting credit is carried out by paying attention to the 5C principle and the 7P principle. What is considered by the judge in handing down decision number 290/Pdt.G/2021/PN Mdn is the Exception of the Defendants, the evidence of the letters submitted by the Plaintiff and the Defendants, the Plaintiff's lawsuit.